Global brand power : leveraging branding for long-term growth - Kahn, Barbara E. (Wharton Executive Essentials., 2013)
The branding bible for today's globalized world. Today, brands have become even more important than the products they represent: their stories travel with lightning speed through social media and the Internet and across countries and diverse cultures. A brand must be elastic enough to allow for reasonable category and product-line extensions, flexible enough to change with dynamic market conditions, consistent enough so that consumers who travel physically or virtually won't be confused, and focused enough to provide clear differentiation from the competition.